The impact of the administration of red ginseng (Panax ginseng) on lipid metabolism and free fatty acid profiles in healthy horses using a molecular networking approach - Kwak, Young Beom; Yoo, Hye Hyun; Yoon, Jungho (Frontiers in Veterinary Science, 2024)
This study investigated the potential benefits of the administration of red ginseng (RG) on lipid metabolism and the profiles of individual free fatty acids (FFAs) in healthy horses.Eight healthy horses, raised under similar conditions, were randomly divided into two groups, each comprising four horses. The experimental group received powdered RG (600 mg/kg/day) mixed with a carrier, and the control group received only the carrier.The parameters associated with lipid metabolism and probable adverse effects were evaluated in both groups after three weeks. The computational molecular networking (MN) approach was applied to analyze the FFA profiles. The results indicated that RG administration significantly reduced blood triglyceride levels in the experimental group.Analysis of the FFAs using MN revealed significant decreases in specific types of FFAs (C12:0, dodecanoic acid; C14:0, myristric acid; C18:1, oleic acid; C18:2, linoleic acid). RG consumption did not produce significant adverse effects on the renal, hepatic, and immune functions. Thus, RG was found to effectively modulate lipid metabolism and the levels of individual FFAs. The application of the MN for the analysis of FFAs represents a novel approach and can be considered for future research.